Inferring divertor plasma properties from hydrogen Balmer and Paschen series spectroscopy in JET-ILW. (19th November 2015) - Lomanowski, B.A.; Meigs, A.G.; Sharples, R.M.; Stamp, M.; Guillemaut, C.
Abstract: A parametrised spectral line profile model is formulated to investigate the diagnostic scope for recovering plasma parameters from hydrogenic Balmer and Paschen series spectroscopy in the context of JET-ILW divertor plasmas. The separate treatment of Zeeman and Stark contributions in the line model is tested against the PPP-B code which accounts for their combined influence on the spectral line shape. The proposed simplified model does not fully reproduce the Stark–Zeeman features for the α and β transitions, but good agreement is observed in the line width and wing profiles, especially for n   >  5. The line model has been applied to infer radial density profiles in the JET-ILW divertor with generally good agreement between the D, , , and lines for high recycling and detached conditions. In an L-mode detached plasma pulse the Langmuir probe measurements typically underestimated the density by a factor 2–3 and overestimated the electron temperature by a factor of 5–10 compared to spectroscopically derived values. The line model is further used to generate synthetic high-resolution spectra for low- n transitions to assess the potential for parameter recovery using a multi-parametric fitting technique. In cases with 4 parameter fits with a single Maxwellian neutral temperature component the D line yields the best results with parameter estimates within 10% of the input values. For cases with 9 parameter fits inclusive of a multi-component neutral velocity distribution function the quality of the fits is degraded. Simultaneous fitting of the D and profiles improves the fit quality significantly, highlighting the importance of complementary spectroscopic measurements for divertor plasma emission studies.